Adaptive information providing system for R&D meeting environments - Rhee, S.K.; Lee, J.; Park, M.-W. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2007)
As extensive amount information is required within a R&D environment, an automated information system could save a considerable amount of time and efforts. There are currently many researches to overcome the information overload phenomenon, including information systems, recommender systems and adaptive hypermedia, and this paper presents an adaptive information providing system utilising some characteristics of these technologies to support R&D and collaborative meeting environments. The system described in this paper aims to present the potential synergy between recommender systems and adaptive hypermedia systems. ？ Springer-Verlag Berlin Heidelberg 2007.